2018
DOI: 10.1371/journal.pone.0195931
|View full text |Cite
|
Sign up to set email alerts
|

The hemodynamic effects of intravenous paracetamol (acetaminophen) vs normal saline in cardiac surgery patients: A single center placebo controlled randomized study

Abstract: The hemodynamic effects of intravenous (IV) paracetamol in patients undergoing cardiac surgery are unknown. We performed a prospective single center placebo controlled randomized study with parallel group design in adult patients undergoing elective cardiac surgery. Participants received paracetamol (1 gram) IV or placebo (an equal volume of 0.9% saline) preoperatively followed by two postoperative doses 6 hours apart. The primary endpoint was the absolute change in systolic (SBP) 30 minutes after the preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Fentanyl and its derivatives show slight mast cell activation and are preferable. Paracetamol (acetaminophen) is not recommended, especially its intravenous administration, because it might cause severe hypotension due to reduction of cardiac output (84).…”
Section: Treatmentmentioning
confidence: 99%
“…Fentanyl and its derivatives show slight mast cell activation and are preferable. Paracetamol (acetaminophen) is not recommended, especially its intravenous administration, because it might cause severe hypotension due to reduction of cardiac output (84).…”
Section: Treatmentmentioning
confidence: 99%
“…Details for included publications are outlined in Table 1. [23][24][25][26] We identified 4 RCTs that enrolled critically ill patients, defined as patients admitted to the ICU or presenting to the ED with a medical emergency. All these studies utilized a placebo control, and 3 of the 4 studies uncovered a clinically significant difference in hemodynamics following IV acetaminophen administration.…”
Section: Resultsmentioning
confidence: 99%
“…Another double-blind RCT that enrolled cardiac surgery patients admitted to inpatient surgical services for coronary artery bypass grafting or mitral or aortic valve repair found similar results. 24 Patients (n = 50) were randomized 1:1 to receive 1 dose of 1000 mg IV acetaminophen or 100 mL of placebo before the index procedure, with additional doses at 6 hours, 12 hours, and conclusion of surgery. Following the preoperative dose, there were a total of 14 hypotensive events, defined by the investigators as a ≥20% reduction in SBP from baseline, all of which occurred in the IV acetaminophen group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent clinical trials have shown that IV paracetamol may cause hypotension in healthy volunteers, the critically ill, and in cardiac surgery patients [ 2 5 ]. The hypotensive effects of IV paracetamol appear to be independent of the excipient mannitol (3.9 g), which is included as a stabilization agent in many of the commercially available IV paracetamol formulations.…”
Section: Introductionmentioning
confidence: 99%